Gender Roles and Culture: Female Students’ Interest in Information Technology Major and Career - Graciela Queen Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Stereotypes has been ingrained in the society for a very long time. According to Daniel Katz and Kenneth Braly (1933), stereotyping guides to racial discrimination just after people respond to a particular group and assign the characteristic of the group emotionally. Cultural expectations have dominated societies around the world, and become an obstacle to women, including in career. However, they start to break down the barriers to show how traditional gender roles belong in the past. Therefore, in college majors, they started to enter the male-dominated majors. This research aims to find out what cultural values do the female students believe related to gender roles and its relationship with their chosen major and career. The theory that will be used is gender roles. A qualitative approach will be used by interviewing and collecting all the data from the students who are majoring in Informatics Engineering and Business Information System (SIB) in Petra Christian University.Keywords: gender roles, non-traditional career, male-dominated majors, education, career choice